[Loading an ox cart] - Ross, W.C. (W.C. Ross and Co., Ltd., 2010)
Estate labourers load an ox cart while some other men look on.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Working class--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Oxen--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Men--Trinidad and Tobago